Variants in genes belonging to the fibroblast growth factor family are associated with lower extremity amputation in non‐Hispanic whites: Findings from the chronic renal insufficiency cohort study. Issue 4 (20th June 2016) - Gupta, Jayanta; Mitra, Nandita; Townsend, Raymond R.; Fischer, Michael; Schelling, Jeffrey R.; Margolis, David J.
Abstract: Diabetes is the major risk factor for nontraumatic lower extremity amputation (LEA). The role of genetic polymorphisms in predisposing diabetics to impaired wound healing leading to LEA has not been sufficiently explored. We investigated the association between a set of genes belonging to the angiogenesis/wound repair pathway with LEA in the Chronic Renal Insufficiency Cohort, a study of adults with chronic kidney disease (CKD) that includes a subgroup with diabetes. This study was performed on 3, 772 Chronic Renal Insufficiency Cohort participants who were genotyped on the ITMAT‐Broad‐CARe array chip. A total of 1, 017 single‐nucleotide polymorphisms (SNPs) in 22 genes belonging to the angiogenesis/would repair pathway were investigated. LEA was determined from patient self‐report. The association between genetic variants and LEA status was examined using logistic regression and additive genetic models after stratifying the cohort by race/ethnicity and diabetic status. Unadjusted analyses as well as analyses adjusted for age, sex, estimated glomerular filtration rate, body mass index, peripheral vascular disease, hemoglobin A1c, and population stratification were performed. In non‐Hispanic white participants with diabetes, rs11938826 andrs1960669, both intronic SNPs in the gene basic fibroblast growth factor‐2 ( FGF2 ), were significantly associated with LEA in covariate‐adjusted analysis (OR: 2.83 (95% CI: 1.73, 4.62); p‐ value: 0.000034; Bonferroni adjusted p‐ value: 0.0006) and (OR: 2.61 (95% CI: 1.48, 4.61); p‐ value: 0.00095; Bonferroni adjusted p‐ value: 0.02). In the same subgroup, rs10883688, an FGF8 SNP of unknown functional effect, was also associated with LEA (OR: 1.72 (95% Confidence Interval: 1.14, 2.6); p‐ value: 0.00999; Bonferroni adjusted p‐ value: 0.04). No statistically significant associations were identified in the other ethnic groups. In conclusion, variant/s in FGF2 and FGF8 may predispose diabetics with CKD to LEA. Dysregulation of the FGF2 gene represents an opportunity to understand further, and possibly intervene upon, mechanisms of wound healing in diabetics with CKD.